2004
DOI: 10.1038/sj.onc.1207260
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution analysis of genomic copy number alterations in bladder cancer by microarray-based comparative genomic hybridization

Abstract: We have screened 22 bladder tumour-derived cell lines and one normal urothelium-derived cell line for genome-wide copy number changes using array comparative genomic hybridization (CGH). Comparison of array CGH with existing multiplex-fluorescence in situ hybridization (M-FISH) results revealed excellent concordance. Regions of gain and loss were defined more accurately by array CGH, and several small regions of deletion were detected that were not identified by M-FISH. Numerous genetic changes were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
120
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 50 publications
(54 reference statements)
13
120
1
Order By: Relevance
“…This is consistent with the observation that the presence of the 6p22 amplicon correlates with tumour cell proliferation rate (Tomovska et al, 2001) and with the observed correlation between expression of E2F3 and the Ki67 proliferation marker (Oeggerli et al, 2004). In contrast, we failed to find evidence to support the view that CDKAL1 represents the bladder cancer oncogene within the 6p22 amplicon (Hurst et al, 2004): knocking down expression of this gene did not alter the BrdU incorporation. The possibility that CDKAL1, which is consistently overexpressed within the 6p22 amplicon, makes some other contribution to tumour development in bladder cancer cells cannot be excluded.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with the observation that the presence of the 6p22 amplicon correlates with tumour cell proliferation rate (Tomovska et al, 2001) and with the observed correlation between expression of E2F3 and the Ki67 proliferation marker (Oeggerli et al, 2004). In contrast, we failed to find evidence to support the view that CDKAL1 represents the bladder cancer oncogene within the 6p22 amplicon (Hurst et al, 2004): knocking down expression of this gene did not alter the BrdU incorporation. The possibility that CDKAL1, which is consistently overexpressed within the 6p22 amplicon, makes some other contribution to tumour development in bladder cancer cells cannot be excluded.…”
Section: Discussionsupporting
confidence: 90%
“…We also demonstrated that in all these three cell lines, amplification of the E2F3 gene was accompanied by E2F3 mRNA overexpression and high-level expression of the E2F3 proteins. In Northern blot analyses, we first confirmed the observation of Hurst et al (2004) that the amplification of the CDKAL1 gene in these cell lines is also accompanied by mRNA overexpression (Figure 1a). The bladder cancer cell line 5637 that exhibits amplification and overexpression of both E2F3 (Figure 2) and CDKAL1 was then chosen for small interfering RNA (siRNA)-mediated knockdown studies.…”
Section: Knockdown Of Mrna In Bladder Cancer Cells Containing Amplifisupporting
confidence: 75%
See 1 more Smart Citation
“…The most common alterations of the chromosome arms were 9q loss (79%), 9p loss (75%), 11p loss (67%), 20q gain (50%), 17p loss (46%), and 11q loss (38%). Alterations of these regions were also reported in two previous array-CGH studies of bladder cancer (Veltman et al, 2003;Hurst et al, 2004). Homozygous deletions were observed at the locus where clones (9p21) containing the MTAP gene and CDKN2B (p16) gene were mapped in eight tumours of two patients, whereas high-level amplifications were not detected.…”
Section: Array-cgh Analysissupporting
confidence: 74%
“…Davidson et al, 2000;AbdelRahman et al, 2001;Karan et al, 2003;Hurst et al, 2004;Hwang et al, 2004), and more recently array CGH has begun to provide more detail of these losses (e.g. Paris et al, 2003;Douglas et al, 2004;Hurst et al, 2004;Nakao et al, 2004;Garcia et al, 2005). Distal 8p also frequently shows loss of heterozygosity (LOH), which would often reflect loss through unbalanced translocation (for references see Adams et al, 2005).…”
Section: Introductionmentioning
confidence: 99%